Pyrolysis conversion of crown-ether-based covalent networks to kagome metal-organic frameworks on Au(111) and Ag(111) - Yifan Liang; Jianing Wang; Ruoting Yin; Zhengya Wang; Xiaoqing Wang; Jie Meng; Shijing Tan; Chuanxu Ma; Qunxiang Li; Bing Wang (Carbon Trends)
On-surface chemistry provides an efficient approach to construction of diverse covalent architectures with atomic precision, ranging from one-dimensional chains and ribbons to two-dimensional covalent organic frameworks (COFs) and metal-organic frameworks (MOFs) on coinage metal substrates. This study explores a distinct on-surface pyrolysis approach to MOFs derived from a crown ether molecular precursor on Au(111) and Ag(111) surfaces. Utilizing scanning tunneling microscopy (STM) and non-contact atomic force microscopy (nc-AFM) combined with density functional theory (DFT) calculations, we elucidate the adsorption behavior and the characteristic macrocyclic configuration of the crown ether on Au(111). Subsequent surface-catalyzed Ullmann coupling reactions at an annealing temperature of 470 K lead to highly disordered COFs with the formation of four-membered and six-membered rings through dimerization and trimerization. For the Ag(111) surface, further annealing at 520 K initiates a unique dehydrogenative reaction within the macrocyclic rings, resulting in the loss of six hydrogen atoms. At an elevated temperature of 720 K, breaking of the second C−O bonds yields a long-range ordered triphenylene-based MOF structure. Electronic characterizations reveal the presence of both regular and diatomic kagome lattices, together with distinct quantum-dot states emerging in the pore regions. Additionally, we investigate the selective encapsulation of single guest picenes within the MOF structure, emphasizing the potential of triphenylene-based frameworks for advanced applications in sensing and molecular filtering. Our findings provide a comprehensive insight into the chemical reactivity of crown ethers on metal substrates and demonstrate a novel pathway to designing MOFs through an on-surface pyrolysis process.